Methylene blue prevents osteoarthritis progression and relieves pain in rats via upregulation of Nrf2/PRDX1 - Li Jia-wei; Wang Rong-liang; Xu Jia; Sun Kuo-yang; Jiang Hui-ming; Sun Zi-ying; Lv Zhong-yang; Xu Xing-quan; Wu Rui; Guo Hu; Jiang Qing; Shi Dong-quan (Acta Pharmacologica Sinica, 2022)
Oxidative stress-related cartilage degeneration, synovitis, and joint pain play vital roles in the progress of osteoarthritis (OA). Anti- oxidative stress agents not only prevent structural damage progression but also relieve OA-related pain. In this study, we investigated the therapeutic effect of methylene blue (MB), a classical and important anti-oxidant with strong neural affinity. Experimental OA was established in rats by radial transection of medial collateral ligament and medial meniscus (MCLT + MMT) of the right knee joint. The OA rats received intra-articular injection of MB (1 mg/kg) every week starting one week after surgery. We showed that MB administration exerted significant cartilage protection, synovitis inhibition as well as pain relief in OA rats. In human chondrocytes and fibroblast-like synoviocytes, MB significantly attenuated tert-butyl hydroperoxide (TBHP)-induced inflammatory response and oxidative stress. We demonstrated that these effects of MB resulted from dual targets of important antioxidant enzymes, Nrf2 and PRDX1, which also mutually reinforcing and participated in an interaction. Furthermore, we found that calcitonin gene-related peptide (CGRP), a neural inflammatory mediator, was accumulated around the vessel in synovium and subchondral bone in OA rats and in TBHP-treated primary cortical neurons; MB administration significantly inhibited CGRP expression through upregulation of Nrf2 and PRDX1. Taken together, these results suggest that MB ameliorates oxidative stress via Nrf2/PRDX1 regulation to prevent progression and relieve pain of OA.